Experimental validation of an energy balance approach for design of horizontal lifeline systems. Issue 1 (2nd January 2022) - Tashrif, Shazed Mohammad; Lim, Wen Cong; Goh, Yang Miang; Hu, Xinping; Koh, Soo Jin Adrian
Abstract : The energy balance approach is one of the design approaches approved in fall protection standards Z359.6, Z259.16 and SS 607 to ensure that horizontal lifeline systems (HLLSs) are adequately designed. However, this study found that theoretical calculations predicting the total fall distance ( h TFD ) and maximum arrest load (MAL) using an energy balance approach need to be corrected before they can be used safely. Based on the data from 48 drop tests, the authors determined that energy balance calculations differ significantly from the empirical h TFD and MAL values of HLLSs. As a result, further correction factors are introduced into the theoretical calculations to estimate h TFD and MAL conservatively. These correction factors are estimated from a regression equation derived based on experimental results and theoretical calculations.